A new species of Mastiglanis Bockmann 1994 (Siluriformes: Heptapteridae) from the Amazon River basin, Peru - Faustino-Fuster, Dario R.; Ortega, Hernán (Zootaxa, 2020)
Mastiglanis is a genus of heptapterid catfish represented by two valid species. These freshwater species are widely distributed along the Amazon, Orinoco, and Maroni River basins. However, a taxonomic review of specimens collected in the Putumayo and Nanay rivers, Amazon River basin in Peru revealed a new species of Mastiglanis. A morphological analysis was completed for morphometric (36 measurements) and meristic (20 counts) data. Osteological counts and descriptions were made from clear and stained specimens and x-rays images. The new species of Mastiglanis differs from M. asopos and M. durantoni by having a long pelvic fin, short snout, eight branched anal-fin rays, and a higher number of vertebrae and gill rakers. The distribution of the new species is restricted to the upper Amazon River basin.